A complete workflow for utilizing Monte Carlo toolkits in clinical cases for a double‐scattering proton therapy system. Issue 1 (13th November 2018) - Muller, Leland; Prusator, Michael; Ahmad, Salahuddin; Chen, Yong
Abstract: The methods described in this paper allow end users to utilize Monte Carlo (MC) toolkits for patient‐specific dose simulation and perform analysis and plan comparisons for double‐scattering proton therapy systems. The authors aim to fill two aspects of this process previously not explicitly published. The first one addresses the modeling of field‐specific components in simulation space. Patient‐specific compensator and aperture models are exported from treatment planning system and converted to STL format using a combination of software tools including Matlab and Autodesk's Netfabb. They are then loaded into the MC geometry for simulation purpose. The second details a method for easily visualizing and comparing simulated doses with the dose calculated from the treatment planning system. This system is established by utilizing the open source software 3D Slicer. The methodology was demonstrated with a two‐field proton treatment plan on the IROC lung phantom. Profiles and two‐dimensional (2D) dose planes through the target isocenter were analyzed using our in‐house software tools. This present workflow and set of codes can be easily adapted by other groups for their clinical practice.